Effect of a culture-based screening algorithm on tuberculosis incidence in immigrants and refugees bound for the United States: a population-based cross-sectional study - Liu, Yecai; Posey, Drew L; Cetron, Martin S; Painter, John A (Annals of internal medicine, 2015)
Before 2007, immigrants and refugees bound for the United States were screened for tuberculosis (TB) by a smear-based algorithm that could not diagnose smear-negative/culture-positive TB. In 2007, the Centers for Disease Control and Prevention implemented a culture-based algorithm. To evaluate the effect of the culture-based algorithm on preventing the importation of TB to the United States by immigrants and refugees from foreign countries. Population-based, cross-sectional study. Panel physician sites for overseas medical examination. Immigrants and refugees with TB. Comparison of the increase of smear-negative/culture-positive TB cases diagnosed overseas among immigrants and refugees by the culture-based algorithm with the decline of reported cases among foreign-born persons within 1 year after arrival in the United States from 2007 to 2012. Of the 3 212 421 arrivals of immigrants and refugees from 2007 to 2012, a total of 1 650 961 (51.4%) were screened by the smear-based algorithm and 1 561 460 (48.6%) were screened by the culture-based algorithm. Among the 4032 TB cases diagnosed by the culture-based algorithm, 2195 (54.4%) were smear-negative/culture-positive. Before implementation (2002 to 2006), the annual number of reported cases among foreign-born persons within 1 year after arrival was relatively constant (range, 1424 to 1626 cases; mean, 1504 cases) but decreased from 1511 to 940 cases during implementation (2007 to 2012). During the same period, the annual number of smear-negative/culture-positive TB cases diagnosed overseas among immigrants and refugees bound for the United States by the culture-based algorithm increased from 4 to 629. This analysis did not control for the decline in new arrivals of nonimmigrant visitors to the United States and the decrease of incidence of TB in their countries of origin. Implementation of the culture-based algorithm may have substantially reduced the incidence of TB among newly arrived, foreign-born persons in the United States. None.